Five-year Outcomes Among Children Receiving Antiretroviral Therapy in a Community-based Accompaniment Program in Rural Rwanda. Issue 11 (November 2016) - Cyamatare Rwabukwisi, Felix; Hedt-Gauthier, Bethany L.; Ribakare, Muhayimpundu; Mukamana, Joyce; Gatesi, Yvonne; Stulac, Sara; Drobac, Peter; Amoroso, Cheryl L.; Gupta, Neil
Abstract : Of 277 HIV-infected children in rural Rwanda enrolled in a community-based accompaniment program, 95.0% were retained in care 5 years after treatment initiation, with only 9 (3.3%) deaths and 3 (1.1%) defaults. Of 235 (84.8%) children with a documented viral load result, 201 (85.5%) demonstrated viral load suppression (<1000 copies/mL). Abstract : Supplemental Digital Content is available in the text.